Efficacy and safety of roxadustat for the treatment of anemia in non-dialysis chronic kidney disease patients: A systematic review and meta-analysis of randomized double-blind controlled clinical trials - Chen, Ting; Huang, Junyue; Dong, Hui; Xu, Lili; Chen, Caihe; Tang, Yu; Huang, Wenhui (Frontiers in Nutrition, 2022)
Objective: To evaluate the efficacy and safety of roxadustat in the treatment of anemia in non-dialysis-dependent chronic kidney disease (NDD-CKD) patients. Methods: For this systematic review and meta-analysis, we searched for randomized controlled trials (RCTs) of anemia in NDD-CKD patients to assess the efficacy and safety of roxadustat. The primary efficacy endpoint was the proportion of patients who achieved a hemoglobin (Hb) response. Secondary efficacy endpoints were hepcidin, serum iron, serum ferritin (SF), total iron-binding capacity (TIBC), transferrin saturation (TAST), and low-density lipoprotein (LDL). Furthermore, adverse events (AEs) were compared. Meta-analyses were performed using Revman 5.4 software. The quality of the evidence was assessed with the Cochrane risk of bias tool. This study was conducted under a pre-established protocol registered with PROSPERO (registration number: CRD42021252331). Results: Seven studies enrolled 4,764 patients, of whom 2,730 received roxadustat and 2,034 received placebo. The results of this meta-analysis showed that roxadustat increased Hb levels [weighted mean difference (WMD) = 1.43, 95% CI: 1.17 to 1.68, P < 0.001, I2 = 95 %], and Hb response [relative ratio (RR) = 8.12, 95% CI: 5.80 to 11.37, P < 0.001, I2 = 61 %]. In addition, roxadustat significantly increased transferrin TAST. During the treatment period in patients with anemia, the AEs of roxadustat compared with placebo was not statistically significant. Conclusions: Roxadustat can improve anemia in NDD-CKD patients by increasing Hb levels and regulating iron metabolism, but does not increase the incidence of AEs.